Is there a text in this cave?: studies in the textuality of the Dead Sea scrolls in honour of George J. Brooke - Feldman, Ariel; Cioată, Maria; Hempel, Charlotte; Brooke, George J. (Studies on the texts of the desert of Judah, 2017)
Preliminary Material -- Introduction /Ariel Feldman , Maria Cioată and Charlotte Hempel -- Are There Sacred Texts in Qumran? The Concept of Sacred Text in Light of the Qumran Collection /Hanne von Weissenberg and Elisa Uusimäki -- Textual Authority and the Problem of the Biblical Canon at Qumran /Philip S. Alexander -- Reflections on Literacy, Textuality, and Community in the Qumran Dead Sea Scrolls /Charlotte Hempel -- Scribal Bodies as Liturgical Bodies: The Formation of Scriptures in Early Judaism /Judith H. Newman -- Qumran Cave 4: Its Archaeology and its Manuscript Collection /Sidnie White Crawford -- Un nouveau manuscrit de Daniel : 4QDnf = 4Q116a /Émile Puech -- 4Q341: A Writing Exercise Remembered /Joan E. Taylor -- 4Q47 (4QJosha): An Abbreviated Text? /Ariel Feldman -- Memories of Amalek (4Q252 4:1–3): The Imprecatory Function of the Edomite Genealogy in the Dead Sea Scrolls /Kipp Davis -- Texts within Texts: The Text of Jeremiah in the Exegetical Literature from Qumran /Armin Lange -- Text, Intertext, and Conceptual Identity: The Case of Ephraim and the Seekers of Smooth Things /Matthew A. Collins -- Strangers to the “Biblical Scrolls”: Balaam’s Fourth Oracle (Num 24:15–19) and its Links to Other Unique Excerpted Texts /Helen R. Jacobus -- Deriving Negative Anthropology through Exegetical Activity: The Hodayot as Case Study /Carol A. Newsom -- The Tefillin from the Judean Desert and the Textual Criticism of the Hebrew Bible /Emanuel Tov -- Dittography and Copying Lines in the Dead Sea Scrolls: Considering George Brooke’s Proposal about 1QpHab 7:1–2 /Eibert Tigchelaar -- Pseudepigraphy and a Scribal Sense of the Past in the Ancient Mediterranean: A Copy of the Book of the Words of the Vision of Amram /Mladen Popović -- The Textual Growth of the Damascus Document Revisited /Philip R. Davies -- Medieval Hebrew Tellings of Tobit: “Versions” of the Book of Tobit or New Texts? /Maria Cioată -- Some Thoughts on the Relationship between the Book of Jubilees and the Genesis Apocryphon /James C. VanderKam -- Tobit and the Qumran Aramaic Texts /Devorah Dimant -- Metaphor and Eschatology: Life beyond Death in the Hodayot /John J. Collins -- The Book of HGY and Ancient Reading Practices /Jonathan Ben-Dov -- Ritualization and the Power of Listing in 4QBerakhota (4Q286) /Jutta Jokiranta -- Jewish Wisdom in the Hellenistic Period: Towards the Study of a Semantic Constellation /Hindy Najman -- In the Garden of Good and Evil: Reimagining a Tradition (Sir 17:1–14, 4Q303, 4QInstruction, 1QS 4:25–26, and 1QSa 1:10–11) /Jean-Sébastien Rey -- How Should We Feel about the Teacher of Righteousness? /Angela Kim Harkins -- The Teacher of Righteousness and His Enemies /Reinhard G. Kratz -- Index of Ancient Sources -- Index of Subjects.